A Sustainability Model for Family-Focused Practice in Adult Mental Health Services - Allchin, Becca; Weimand, Bente M.; O'Hanlon, Brendan; Goodyear, Melinda (Frontiers in Psychiatry, 2022)
Background Translating evidence-based practice to routine care is known to take significant time and effort. While many evidenced-based family-focused practices have been developed and piloted in the last 30 years, there is little evidence of sustained practice in Adult Mental Health Services. Moreover, many barriers have been identified at both the practitioner and organizational level, however sustainability of practice change is little understood. What is clear, is that sustained use of a new practice is dependent on more than individual practitioners' practice. Design and Method Drawing on research on sustaining Let's Talk about Children in adult mental health services and in the field of implementation science, this article proposes a model for sustaining family focused practice in adult mental health services. Sustainability Model for Family-Focused Practice An operational model developed from key elements for sustaining Let's Talk about Children identifies six action points for Adult Mental Health Services and their contexts to support the sustainability of family-focused practices. The model aims to support Services to take action in the complexity of real-world sustainability, providing action points for engaging with service users and practitioners, aligning intra-organizational activities, and the wider context. Conclusion The model for sustaining family-focused practice draws attention to the importance of sustainability in this field. It provides a practical framework for program developers, implementers, adult mental health services and policy-makers to consider both the components that support the sustainability and their interconnection. The model could be built on to develop implementation guides and measures to support its application.